2016
DOI: 10.1136/bmjopen-2016-012690
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of renin–angiotensin system blockers and risk of acute kidney injury: a population-based cohort study

Abstract: ObjectiveTo investigate whether there is an association between use of ACE inhibitors (ACEI) and angiotensin receptor blockers (ARB) and risk of acute kidney injury (AKI).Study designWe conducted a new-user cohort study of the rate of AKI among users of common antihypertensives.SettingUK primary care practices contributing to the Clinical Practice Research Datalink (CPRD) eligible for linkage to hospital records data from the Hospital Episode Statistics (HES) database between April 1997 and March 2014.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 32 publications
4
68
1
2
Order By: Relevance
“…Patients concomitantly prescribed diuretics and NSAIDSs are at greater risk of AKI, as observed by others . Amongst incident patients prescribed ACEi/ARB medication, we found a similar rate of AKI episodes associated with a hospital admission to a previous cohort of ACEi/ARB users . The incidence of biochemical AKI based on internationally recognised creatinine change criteria was approximately twofold higher than has previously been reported for the general population in the Grampian region …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Patients concomitantly prescribed diuretics and NSAIDSs are at greater risk of AKI, as observed by others . Amongst incident patients prescribed ACEi/ARB medication, we found a similar rate of AKI episodes associated with a hospital admission to a previous cohort of ACEi/ARB users . The incidence of biochemical AKI based on internationally recognised creatinine change criteria was approximately twofold higher than has previously been reported for the general population in the Grampian region …”
Section: Discussionsupporting
confidence: 83%
“…There would be biases in selecting a group of patients commenced on an alternative class of antihypertensive medication such as calcium channel blockers. This has been explored in other studies with only small increases of AKI incidence with ACEi/ARB in comparison to patients exposed to antihypertensive regimes not including ACEi/ARB . In the case of HF, it would be unusual not to be treated with ACEi/ARB therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have demonstrated that C20 suppressed renin expression under normal levels of calcium and phosphorus in vivo, which further indicated the beneficial role of C20 on renal protection. The down-regulation of renin expression markedly ameliorated the renal and cardiomyocyte injury [39,42].…”
Section: Discussionmentioning
confidence: 99%
“…The most robust observational evidence comes from population-based cohort studies where baseline comorbidities and other drug use can be accounted for. Recent studies of this type have shown weak or no association between ACEI/ARB use and AKI (3,4). However, patients with comorbidities for which ACEIs/ARBs are indicated (e.g., diabetes, HFrEF, and CKD) are at high risk of AKI, with rates increasing as the list of comorbidities grows (3).…”
mentioning
confidence: 99%